Uplift of very sensitive soft clay due to pile driving - W. Teparaksa; J. Teparaksa (International Association of Lowland Technology, 2018)
The subsoil of Samutprakarn province in Thailand consists of thick sensitive very soft clay layer. The construction, such as pile driving and excavation work would lead to reduce the shear strength of very soft clay or induce the excess pore pressure on very soft clay. This paper presents the results of pile driving around the press pit reinforced concrete structure which was excavated and constructed on the very soft sensitive clay. The pile driving effect surrounding the press pit caused the uplift of press pit. The uplift of press pit was investigated by additional soil investigation, piezometer installation as well as coring the base slab of press pit. The investigation result was analyzed for clarifying the uplift behaviors before remedial work. At present, the remedial work was already completed.